Estudio de Métodos y tiempos para el Mejoramiento en la entrega de Servicios de Calibración de los instrumentos en la Empresa XYZ. (2023)
Although it is true, when companies apply a methodology which is used in the deep analysis of processes where there are complications such as bottlenecks, according to the evolution of history in industrial engineering, these companies found how to know and identify those times that affect your productivity. This method focused on the study of times and movements within the process itself provides the minimum details of each movement within the executed activity; and thanks to this information it can be adapted with certain improvements solving the failures or shortcomings found. In this way, they will optimize their times, which represents an increase in productivity.